Detection, assessment, and updating the maps of encroached forest areas: a case study from Bara district, Nepal - Rimal, R. K.; Maharjan, R.; Khanal, K.; Koirala, S.; Karki, B.; Nepal, S. M.; Shrestha, H. L. (Banko Janakari, 2017)
Forest encroachment is an illegal expansion of cultivable land and settlements within the jurisdiction of forests. It has been the key threat to forest management for the last several years in Nepal. The Department of Forests (DoF) is the responsible authority for detection and assessment of forest encroachment throughout the nation and updating the forest maps accordingly. Detection and preparing the updated maps of encroached forest areas is necessary for sustainable management of forests. Traditionally, the extent of forest encroachment is assessed through estimation by the front-line forestry staff. The new approach combines the aerial photographs, the cadastral maps prepared by the Department of Survey and the Google Earth Imagery to spatially locate the encroachment. This method will work as a desktop tool for the forest manager such that appropriate strategic actions can be taken immediately. Additionally, it will bring a transparency on the forest governance to identify the location of areas of interest like point location for forest-based industries or proposed sites for development of infrastructures on the ground. The local communities may use the tool to identify the actual location of the forest boundaries, and exert social pressure to relinquish the encroached forests, if any. The result showed that 8,540 ha of the forest area in Bara district was found to be encroached during the period of last 50 years, between 1964 and 2014, of which 71% (6,038 ha) happened to be encroached in the first three decades, indicating the retarding trend of encroachment in the later years. The methodology used to assess the encroachment of forest in Bara district can be easily scaled up to other districts too, and will eventually help to assess the country’s overall forest encroachment. Since the boundary delineation will be done on the basis of the cadastral maps, the output will be used as a robust evidence to defend the forest-related cased in the court during the legal arbitrations. Banko Janakari, Vol. 27, No. 1, Page: 65-71